2004
DOI: 10.1002/cncr.20628
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation among patients with leukemia of all ages in Texas

Abstract: BACKGROUNDHematopoietic stem cell transplantation (HSCT) is an effective but expensive medical procedure to which some ethnic minorities, the elderly, and those without insurance have been shown to have limited access. The purpose of the current study was to determine whether socioeconomic factors were associated with HSCT usage rates in patients with leukemia.METHODSThe authors identified 6574 patients with acute lymphocytic leukemia, chronic lymphocytic leukemia, acute myelogenous leukeima, chronic myelogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Consistent with findings made by others [10,14], chemotherapy and HCT utilization reported here were lowest among older acute leukemia patients with further reduced treatment utilization observed among older patients that were not married. Reasons for reduced utilization of HCT in older patients may include lower suitability for chemotherapy and HCT because of poor performance status, increased acuity at presentation, and comorbidities that lower tolerance for aggressive treatment [36], although physician biases and nihilism [9] regarding the value of chemotherapy and HCT in the older population may also play a role despite growing evidence that the older population can benefit from chemotherapy and HCT.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with findings made by others [10,14], chemotherapy and HCT utilization reported here were lowest among older acute leukemia patients with further reduced treatment utilization observed among older patients that were not married. Reasons for reduced utilization of HCT in older patients may include lower suitability for chemotherapy and HCT because of poor performance status, increased acuity at presentation, and comorbidities that lower tolerance for aggressive treatment [36], although physician biases and nihilism [9] regarding the value of chemotherapy and HCT in the older population may also play a role despite growing evidence that the older population can benefit from chemotherapy and HCT.…”
Section: Discussionsupporting
confidence: 93%
“…Multivariable analyses of HCT utilization among acute leukemia patients using hospital discharge data for 1988 and 1991 showed that odds of HCT for acute leukemia were negatively influenced by older age, black race, self-pay status, Medicaid insurance, and HMO insurance 10 . In contrast, a large study using Texas hospital discharge data from 1999 found no difference in utilization of HCT based on race or insurance status [14]. Evaluating more recent data, Joshua et al .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined access to transplants in patients with leukemia, lymphoma and multiple myeloma by race. There are conflicting data in the literature, vwth less frequent transplants in black patients in some studies [22,23], but not others [24]. Of note, these prior studies did not include patients with MDS.…”
Section: Discussionmentioning
confidence: 96%
“…85 This was confirmed in a second study, 86 although another report found no difference. 87 However, once the patient is referred for HCT, how would black race lead to a negative impact on transplantation outcome? [88][89][90] In an analysis of 2221 allogeneic transplantation recipients, black race was associated with significantly higher mortality rates than observed in whites (HR ϭ 1.65).…”
Section: Race and Socioeconomic Statusmentioning
confidence: 99%